Penguatan Layanan Kebidanan Esensial pada Kondisi Darurat dan Pasca Bencanadi Desa Nogosari, Kecamatan Pacet, Kabupaten Pasuruan, Provinsi Jawa Timur - Elga Ceisaria Andani; Miftahul Khairoh; Arkha Rosyaria Badrus; Rakhmalia Imeldawati; Ainun Ganisia; Nurul Fathiyyah; Shinta Nur Rochmayati; Kholifatul Ummah; Alief Ayu Purwitasari (Rena Cipta Mandiri, 2025)
Emergency and post-disaster conditions often disrupt essential midwifery services, directly affecting the safety of mothers and newborns. Limited access to health facilities, shortages of healthcare personnel, and weak referral systems are major barriers to maternal and neonatal care in disaster-prone areas. This Community Service Program was conducted in Nogosari Village, Pacet District, Pasuruan Regency, East Java, to strengthen the preparedness of midwifery services. The methods included cross-sector coordination, community education, capacity building for supporting personnel, mentoring of health cadres, and simulation of essential midwifery service pathways in crisis situations. The activities focused on the provision of basic midwifery services, continuity of care for pregnant women, childbirth, postpartum mothers, and newborns, as well as strengthening the referral system. The results showed increased knowledge, skills, and preparedness among community members, cadres, and volunteers in maintaining essential midwifery services during emergencies. In addition, a shared understanding was developed regarding the importance of continuity of midwifery care as a form of protection for vulnerable groups. This program strengthened the resilience of community-based midwifery service systems and supported efforts to reduce maternal and neonatal morbidity and mortality risks in disaster situations. Furthermore, the activity encouraged sustainable collaboration among healthcare workers, village authorities, and the community to maintain adaptive and responsive midwifery services in the future.